Direct relationship between transvalvular velocity and cardiac dysfunction, morbidity, and mortality in patients with aortic stenosis. Issue 12 (15th November 2022) - Yousef, Sameh; Amabile, Andrea; Ram, Chirag; Singh, Saket; Agarwal, Ritu; Milewski, Rita; Assi, Roland; Patel, Prakash A.; Krane, Markus; Geirsson, Arnar; Vallabhajosyula, Prashanth
Abstract: Objective: Current guidelines recommend intervention in subjects with severe symptomatic aortic stenosis (AS), even though any degree of AS is associated with a higher risk of mortality. We investigated the association between the degree of AS, delineated by transvalvular flow velocity, and patient morbidity and mortality. Methods: Medically managed patients aged 40–95 years with maximum flow velocity ( V max ) by echocardiography between 2013 and 2018 were stratified into five groups (A–E) based on the 75th, 90th, 97.5th, and the 99th percentiles of V max distribution. Patient characteristics, cardiac structural changes, and end‐organ disease were compared using Kruskal–Wallis and Cochran–Armitage tests. Mortality over a median of 2.8 (1.52–4.8) years was compared using Kaplan–Meier curves and risk estimates were derived from the Cox model. Results: The V max was reported in 37, 131 patients. There was a steady increase (from Group A towards E) in age, Caucasian race, structural cardiac changes, end‐organ morbidities, and all‐cause mortality. In reference to Group A, there as an increased risk of mortality in Groups B (hazard ratio [HR] = 1.3; confidence interval [CI]: 1.2–1.35;  p  < .0001), C (HR = 1.5; CI: 1.4–1.6; p  < .0001),  and D (HR = 1.8; CI: 1.6–2;  p  < .0001), with an exponential increase in Group E (HR = 2.5; CI: 2.2–2.8; p  < .0001). Conclusions: A direct, strong correlation exists between the degree of AS and cardiac structural changes and mortality. Patients with V max  ≥ 97.5th percentile (≥3.2 m/s) might benefit from early intervention.